DIFFERENTIAL DIAGNOSIS IN JUVENILE SCLERODERMA - M.K. Osminina; N.A. Geppe; N.S. Podchernyaeva; G.M. Rabieva; G.V. Tugarinova (Вопросы современной педиатрии)
Scleroderma is a rare rheumatic disease. Clinical symptoms and syndromes of scleroderma in children are presented. Different tialbdiagnostic search in case of main clinical, instrumental and laboratory implications of disease is given. Peculiarities of children's scleroderma are shown.Key words: children, juvenile scleroderma, symptoms, syndromes, differential diagnosis.